FACTORS AFFECTING TEACHERS’ USE OF ICT IN FOREIGN LANGUAGE TEACHING IN VIETNAM (Journal of Foreign Language Studies, 2024)
Through the lens of the Unified Theory of Acceptance and Use of Technology, the results of a recent case study at Hanoi University show that foreign language teachers’ use of ICT can be impacted by four main factors: performance expectancy, effort expectancy, social influence and facilitating conditions. These factors are unpacked in more depth, leading to the suggestion that ICT training and leadership support should be the key to successful integration of ICT in the time to come.